2012
DOI: 10.1093/rheumatology/ker431
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of major salivary glands could be an alternative tool to sialoscintigraphy in the American-European classification criteria for primary Sjogren's syndrome

Abstract: US finding of major salivary gland involvement could replace sSC in AEC for the diagnosis of pSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 17 publications
0
51
0
8
Order By: Relevance
“…Furthermore, Giuseppetti et al (2005) reported that contrastenhanced ultrasound can provide additional information in morphologic and functional parotid imaging. Most of the previous studies on salivary gland ultrasound in SS deal with the contribution of B-mode sonography to diagnosis and focus on different scoring systems or the potential to replace the aforementioned established modalities, which are part of different classification criteria (Cornec et al 2013(Cornec et al , 2014Hocevar et al 2005;Kawamura et al 1990;Milic et al 2012;Niemela et al 2004;Takashima et al 1992;Wernicke et al 2008;Yonetsu et al 2002). Meanwhile, there are various validated scoring systems for B-mode sonography, with just marginal differences regarding the evaluation of salivary gland echostructure, which seems to be the most characteristic alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Giuseppetti et al (2005) reported that contrastenhanced ultrasound can provide additional information in morphologic and functional parotid imaging. Most of the previous studies on salivary gland ultrasound in SS deal with the contribution of B-mode sonography to diagnosis and focus on different scoring systems or the potential to replace the aforementioned established modalities, which are part of different classification criteria (Cornec et al 2013(Cornec et al , 2014Hocevar et al 2005;Kawamura et al 1990;Milic et al 2012;Niemela et al 2004;Takashima et al 1992;Wernicke et al 2008;Yonetsu et al 2002). Meanwhile, there are various validated scoring systems for B-mode sonography, with just marginal differences regarding the evaluation of salivary gland echostructure, which seems to be the most characteristic alteration.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that more emphasis should be given to tests that in addition to identifying true cases and excluding unaffected individuals, can be done at early stages, multiple times, and with minimal distress to the participant 29. In the future, we may see salivary gland ultrasonography playing this role in SS 30. But with the current sets of criteria, there is an interesting difference in terms of accessibility; while the ACR criteria require evaluation by a practitioner specialising in eyes and by a practitioner who can perform a lip biopsy, both the Schirmer's and the WUSF tests can be performed in a standard medical office without the need for sophisticated equipment or medical specialists.…”
Section: Discussionmentioning
confidence: 99%
“…A number of publications have presented convincing data on the usefulness of SGUS for diagnosis of primary SS (7)(8)(9)(10)(11). Various scoring systems evaluating size of the glands, parenchymal echogenicity and inhomogeneity, clearness of the borders, and vascularity were proposed (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%